2019
DOI: 10.3389/fgene.2018.00701
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Conserved Transcriptional Networks Underlying Pesticide Exposure and Parkinson's Disease: A Focus on Chemicals of Epidemiological Relevance

Abstract: While a number of genetic mutations are associated with Parkinson's disease (PD), it is also widely acknowledged that the environment plays a significant role in the etiology of neurodegenerative diseases. Epidemiological evidence suggests that occupational exposure to pesticides (e.g., dieldrin, paraquat, rotenone, maneb, and ziram) is associated with a higher risk of developing PD in susceptible populations. Within dopaminergic neurons, environmental chemicals can have an array of adverse effects resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 164 publications
(222 reference statements)
0
16
0
Order By: Relevance
“…In this context, the widely used herbicide paraquat (PQ) has been shown to exhibit neurotoxic effects that closely mimic the parkinsonian phenotype. , Different epidemiological studies have shown that chronic exposure to PQ increases the risk of PD. , PQ is known to induce elevated oxidative stress and has been shown to cause degeneration of DA-ergic neurons in the SN region of the brain . The link between PQ exposure and risk of PD has been further cemented by various studies conducted in cellular and animal models. Not only have such studies provided important insight in deciphering the etiology of PD, but also such a PQ-induced PD phenotype mimicking animal model serves as an efficient tool to study the potential of novel therapeutic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the widely used herbicide paraquat (PQ) has been shown to exhibit neurotoxic effects that closely mimic the parkinsonian phenotype. , Different epidemiological studies have shown that chronic exposure to PQ increases the risk of PD. , PQ is known to induce elevated oxidative stress and has been shown to cause degeneration of DA-ergic neurons in the SN region of the brain . The link between PQ exposure and risk of PD has been further cemented by various studies conducted in cellular and animal models. Not only have such studies provided important insight in deciphering the etiology of PD, but also such a PQ-induced PD phenotype mimicking animal model serves as an efficient tool to study the potential of novel therapeutic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, given the differentially methylated promoter of the TNF- α gene in PD [ 23 ], the role of cigarette smoking in this relationship should be further explored. Additionally, smoking seems to affect histone acetylation and de-acetylation, and affect the expression of miRNAs in non-nerve tissues [ 82 , 83 , 84 , 85 ]. Thus, DNA methylation and possibly other epigenetic modifications might mediate the effects of smoking in PD.…”
Section: Environmental Impact On Epigenetic Modifications In Pdmentioning
confidence: 99%
“…Chronic organochlorine, organophosphate, paraquat and pyrethroid exposures have been linked to Parkinson's disease and other neurodegenerative diseases through mitochondrial dysfunction, oxidative stress, and apoptosis via cell signaling pathways (Cao et al, 2019). Some pesticides have been reported as potential risk factors of chronic erectile dysfunctions (Polsky et al, 2007), probably via NADPH oxidase/ROS production and reduced bioavailability of NO (Jin and Burnett, 2008).…”
Section: Xenobiotics and Viruses Have Common And More Than One Mechanisms Of Actionmentioning
confidence: 99%